EFEKTIVITAS PELAKSANAAN TUGAS BAPERJAKAT DALAM RANGKA PENGANGKATAN PEGAWAI PADA JABATAN STRUKTURAL DIKABUPATEN HALMAHERA UTARA - Eintemon, Sugianto (Sam Ratulangi University, 2013)
ABSTRACT : Baperjakat an important element in creating a theory of the right man on the right job, the right man on the right place. One way to realize this theory is the appointment of civil servants in a structural position for placement of civil servants in the structural position can increase the knowledge, skills, increase motivation and morale, and improve organizational productivity. Issues to be addressed in this study is the effectiveness of the implementation of tasks in the framework of the appointment of civil servants Baperjakat on structural position. This study uses qualitative methods.This study aims to describe, analyze and determine whether the performance of duties baperjakat team in the appointment of civil servants in the structural position has been effective indicators of job analysis, discipline, work experience, knowledge and skills and the development of human resources.Results of research conducted through the collection of data obtained through observation and interviews are: (1) job competence, (2) knowledge and skills possessed by structural, (3) before the performance of civil servanUGIANts in the shallow structural position. Based on the research that the implementation of tasks in order baperjakat appointment of civil servants are effective in structural positions in accordance with the rules in force. Based on the research conclusions, suggested again Baperjakat still need to be selective in terms of the appointment of civil servants because of the principle of